The Relationship of Nurses Response Time to Patient's Statisfaction in Emergency Department - Antara, I Gusti Ngurah Putu Jaya; Arista, Putu Dina; Yuliani, Ni Made Erna; Susiladewi, Ida Ayu Md. Vera; Artawan, I Kadek (Babali Publisher, 2023)
Emergency department (ED) is one part of the hospital that provides initial services for patients suffering from illnesses and injuries that can threaten their survival. In its role to increase patient satisfaction in ED must be able to provide quality service consistently. The length of time to respond (response time) is very important in the service of emergency patients and certainly affects the quality of life and patient satisfaction. This study aims to determine the Relationship of Nurses Response Time to Patient Satisfaction in ED of Bali Mandara Hospital. The research design used in this study is an analytic survey. By using a Cross Sectional Study approach. A sample of 87 respondents will be selected using the accidental sampling method sampling technique. Data collection tools using nurses response time observation sheets and patient satisfaction questionnaires that have been tested valid and reliable. The results showed that the nurses response time in ED was in the fast category (≤5 minutes) 68 respondents (78.2%), 66 respondents (75.9%) were satisfied. The results of the chi-square statistical test obtained p-value = 0.007, where p <α (α = 0.05) so it was concluded that there was a significant relationship between nurses response time and patient satisfaction in ED.